Effect of mild sedation and analgesia on radial artery cannulation in novice residents: a prospective, randomized controlled trial - Ya-zhi Xi; Zhen-ping Li; Qing-he Zhou (BMC Medical Education)
Abstract Background Radial artery cannulation can be challenging, particularly for inexperienced providers. This study aimed to compare the success rates of resident physicians performing radial artery cannulation with mild sedation and analgesia versus without. Materials and methods This study was a prospective, single-center, double-blind randomized controlled trial. Twelve anesthesiology residents performed radial artery insertions on 96 patients. The procedures were conducted with either mild sedation and analgesia (treatment group) or an equivalent volume of 0.9%Nacl (control group), in a random order. The primary outcome was the success rate of radial artery cannulation within 10 min for each group. Secondary outcomes included the first-attempt success rate, visual analogue scale (VAS) scores, and self-reported patient discomfort scores (0 corresponding to “no anxious”, 1 corresponding to “mildly anxious”, 2 corresponding to “moderately anxious” and 3 corresponding to “very anxious”). Results The success rate of radial artery cannulation within 10 min was 75.0% (36/48) in the treatment group and 54.2% (26/48) in the control group, respectively (difference 20.8%; P = 0.033, OR: 1.38, 95%CI: 1.02–1.88). The first-attempt success rate was 68.8% (33/48) in the treatment group, compared to 52.1% (25/48) in the control group (difference 16.7%; P = 0.095, OR: 1.32, 95%CI: 0.95–1.84). The VAS scores and self-reported patient discomfort scores were significantly lower in the treatment group than in the control group (2.0 [2.0, 2.0] vs. 3.0 [2.0, 4.0], P = 0.005; 1.0 [0.0, 2.0] vs. 2.0 [2.0, 2.0], P<0.001, respectively). Conclusions The success rate of radial artery cannulation within 10 min significantly increased for anesthesiology residents with the use of mild sedation and analgesia. Additionally, these medications resulted in a notable reduction in procedure-related pain and patient discomfort. Trial registration The study was registered at ClinicalTrials.gov (NCT05863455), with Qing-he Zhou as the principal investigator, on May 16, 2023.